Trajectories of socioeconomic inequality in early child development: a cohort analysis - Tanja A. J. Houweling; Joost Oude Groeniger; Pauline W. Jansen; Pol van Lier; Nil Horoz; Marieke Buil; Frank J. van Lenthe (BMC, 2022)
Abstract Background Addressing socioeconomic inequalities in early child development (ECD) is key to reducing the intergenerational transmission of health inequalities. Yet, little is known about how socioeconomic inequalities in ECD develop over the course of childhood. Our study aimed to describe how inequalities in ECD by maternal education develop from infancy to middle childhood. Methods We used data from Generation R, a prospective population-based cohort study in The Netherlands. Language skills were measured at ages 1, 1.5, 2, 3, and 4 years, using the Minnesota Child Development Inventory. Socioemotional (i.e. internalizing and externalizing) problems were measured at ages 1.5, 3, 5 and 9 years using the Child Behavior Checklist. We estimated inequalities in language skills and socioemotional problems across the above-mentioned ages, using linear mixed models with standardized scores at each wave. We used maternal education as indicator of socioeconomic position. Results Children of less educated mothers had more reported internalizing (B = 0.72, 95%CI = 0.51;0.95) and externalizing (B = 0.25, 95%CI = 0.10;0.40) problems at age 1.5 years, but better (caregiver reported) language skills at 1 year (B = 0.50, 95%CI = 0.36;0.64) than children of high educated mothers. Inequalities in internalizing and externalizing problems decreased over time. Inequalities in language scores reversed at age 2, and by the time children were 4 years old, children of less educated mothers had substantially lower language skills than children of high educated mothers (B = -0.38, 95%CI = -0.61;-0.15). Conclusions Trajectories of socioeconomic inequality in ECD differ by developmental domain: whereas inequalities in socioemotional development decreased over time, inequalities increased for language development. Children of less educated mothers are at a language disadvantage even before entering primary education, providing further evidence that early interventions are needed.